Gas–Liquid Flow Behavior in Condensate Gas Wells under Different Development Stages - Weiyang Wang; Wei Zhu; Mingzhong Li (Energies, 2023)
The phase state prediction methods of condensate gas are relatively mature, but the effect of phase changes on gas–liquid mixture flow behavior and the liquid-carrying capacity of gas has not been researched in detail. This study applied PIPESIM software to predict the fluid phase properties under different development stages of a condensate gas reservoir in Shengli Oilfield and determined the phase diagram and physical properties of the well stream on the basis of the optimized equation of state (EOS). Then the influence of phase change characteristics on wellbore flow behavior and critical liquid-carrying gas velocity was analyzed. The study showed that compared with the early development stage, fewer heavy components are produced and the produced gas–liquid ratio is increased in the late stage of the condensate gas reservoir. In addition, the pressure loss of fluid is decreased, the critical liquid-carrying gas velocity and flow rate are reduced, and the liquid-lifting difficulty is reduced for gas. The reason is that the liquid density decreases obviously due to the phase change, while the gas density is almost unchanged, and the oil–gas surface tension decreases obviously, resulting in a decrease in the critical liquid-carrying gas velocity. At the same time, the variation in the gas compressibility factor is very small, which leads to a decrease in the critical liquid-carrying gas flow rate.